Upper body power in cross-country skiing - Rundell, K. W.
Since the advent of the skating technique in cross-country ski racing, emphasis on upper body fitness has gradually become a critical component of cross-country ski training. A major focus of this training has been on the development of short-term double poling power output. This focus has primarily come about because of recent research. Several researchers have shown that effective upper body power output during ski skating relates strongly to race velocity and competitive results. Olympic and World Championship medal winning Russian Biathletes tested at the Lake Placid Olympic Training Center demonstrated modest VO2max values (a measure of aerobic capacity, that were not different than U.S. National Team members), but 30% higher short-tern double pole power outputs than U.S. Biathletes. Additionally, ski times at U.S. Biathlon National Championships have been highly related to upper body power (R=0.95, an "R¾ of 1.0 is a perfect relationship), but not VO2max. Recent work by Steve Gaskill, Bob Serfass, and Ken Rundell extended this concept by including a large population of skiers with varied abilities. This study demonstrated a strong relationship (r=0.90) between upper body power and race velocity in 158 Minnesota high school skiers. The results of these studies support a structured upper body training regimen to improve upper body power in developmental and elite skiers.